Não há que ser flexível, há que ser forte: um estudo sobre os limites no trabalho e na família - Furtado, Liliane Magalhães Girardin Pimentel (2012)
A growing number of people have dealt with work and family responsibilities in the daily routine. This scenario has led to more research on the relationship between work and family and its impact on individuals and organizations. There are several approaches and theoretical perspectives to explain the relationship between these domains. They analyze the effects that work and family can cause each other. The present research addresses the work-family interface from the study of the boundaries created by individuals in these domains. Boundaries directly influence the way the work-family interface is built. Research hypotheses are developed to explore the work-family boundary strength construct, its antecedents and its relationship to the work-family conflict and occupational stress. It also proposed a moderating effect of social support in the relationship between work-family conflict and occupational stress. To test the empirical validity of the proposed model, 401 brazilians employees were surveyed using structured questionnaires. Data analyses suggest that strong boundaries at work and at family are associated with low levels of work-family conflict and low levels of occupational stress. The results also support the moderating role of social support (supervisor support and coworker support) on the relationship between work-family conflict and occupational stress. It is expected that these results expand the focus of analysis of work-family interface and help in understanding the theory and organizational practice.